Groundwater Quality Assessment in Ranjangaon Shenpunji Village of Aurangabad, Maharashtra, India - Kamble S. N.; Sirsat S. K. (Emerging Issues in Environment, Geography and Earth Science Vol. 9, 2024)
The present study was carried out to in Rajangaon Shenpunji village for assessment of groundwater quality. Thirty groundwater samples were collected from dug and bore wells for this water quality analysis and eleven physico-chemical parameters i.e. PH, EC, TDS, CL, TH, Mg, Ca, HCO3, Na, K and SO4were calculated by using standard methods and instruments. From the water quality analysis 100% groundwater samples are exceeding maximum permissible limit except TDS 40%, Cl 30%, Mg 73.33% and Sulphate 76.67% is exceeding maximum permissible limit as per WHO and BIS standards level for drinking water.Plot the major cations and ions in the piper triangular diagram and it shows that 100% groundwater samples are fall in Ca-Cl water type. This study provides information for groundwater chemistry in Rajaongaon Shenpunji village industrial area. Its need to focus on the specific contamination source and it migrate in groundwaters.